Asymmetric Relations Between Indonesia and Singapore - Mohammad Mohtar Mas’oed (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2024)
The effort to repatriate funds stored abroad by Indonesian citizens, as part of the 2016 Tax Amnesty Program by the government, was deemed a failure. Only 14% of the expected funds were brought back into the country. This is very disappointing, considering the government needs substantial funds to support the financing of Indonesia's economic development, especially physical economic infrastructure development. Given that a significant portion of the funds held abroad by Indonesians is in Singapore and that the Indonesian government had requested Singapore's assistance to facilitate the repatriation of these funds, this phenomenon raises interesting questions. There are even suspicions that the Singaporean government did not care enough, and may have even hindered these repatriation efforts. This paper attempts to highlight this issue and place it within the study of a central concept in political science and international relations, namely power. Considering physical geographical size (Indonesia being the largest), demographic (the largest population), and economic (the largest GDP), why can the much larger country not influence the smaller one? Why is “Goliath” powerless in front of “Lilliput”? This case triggers a theoretical discussion about the meaning of power in political science and international relations analysis. How is power discussed in this body of knowledge? Among the various approaches in the literature, one that aptly describes the situation where the